2016
DOI: 10.1080/01635581.2016.1152383
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Reduces Cancerogenic Potential of Renal Cancer Cells via Geranylgeranyl Pyrophosphate and Mevalonate Pathway

Abstract: Simvastatin is a cholesterol-lowering drug, inhibiting 3-hydroxy-3-methylglutaryl-coenzyme CoA (HMG-CoA) reductase. Previous studies have indicated the anticancerous effects of simvastatin. Here, we evaluated the anticancerous potential of simvastatin in renal cell carcinoma (RCC) cell lines. RCC occurs with an incidence of 2-3% of all cancer entities with high chemoresistance rate. Therefore, the understanding of underlying mechanisms for RCC activity and the development of alternative therapies are essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Enhanced cholesterol biosynthesis has been shown to play a role in prostate cancer development (reviewed by Hager et al [19]), for example, and blocking the mevalonate pathway may have antineoplastic potential [20][21][22]. While epidemiological evidence on statin use and cancer survival are as yet inconclusive [23,24], some preclinical trials of mevalonate pathway inhibitors have shown promising effects as primary or adjuvant therapy in several malignancies, including ovarian cancer [25,26], breast cancer [22,27], and renal cell carcinoma [28]. Despite these promising developments, clinical trials have not yet demonstrated consistently significant benefits for patients treated with mevalonate pathway inhibitors [29].…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced cholesterol biosynthesis has been shown to play a role in prostate cancer development (reviewed by Hager et al [19]), for example, and blocking the mevalonate pathway may have antineoplastic potential [20][21][22]. While epidemiological evidence on statin use and cancer survival are as yet inconclusive [23,24], some preclinical trials of mevalonate pathway inhibitors have shown promising effects as primary or adjuvant therapy in several malignancies, including ovarian cancer [25,26], breast cancer [22,27], and renal cell carcinoma [28]. Despite these promising developments, clinical trials have not yet demonstrated consistently significant benefits for patients treated with mevalonate pathway inhibitors [29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, statins inhibit tumor cell invasion, migration, and metastasis by attenuating the geranylgeranylation and activation of Rho oncoproteins (Al-Haidari et al, 2014; Kato et al, 2018). Conversely, mevalonate and GGPP abolished statin-induced effects on p-AKT, p-ERK, cell cycle arrest, and apoptosis in several tumors including human HL-60 leukemia cells (Chen et al, 2015), ovarian cancer cells (de Wolf et al, 2017), MiaPaCa-2 pancreatic cancer cells (Gbelcova et al, 2017), Caki-1 and KTC-26 renal carcinoma cells (Woschek et al, 2016), and malignant anaplastic thyroid cancer (Chen et al, 2017). By blocking the synthesis of mevalonate-derived metabolites that hinder the ubiquitination and degradation of mutant p53 protein, statins also suppress the growth of mutant p53-expressing cancer cells (Freed-Pastor et al, 2012; Freed-Pastor and Prives, 2016; Parrales et al, 2016).…”
Section: Effects Of Statins On Cancer Growth With Dose-limiting Toxicmentioning
confidence: 99%
“… 30 Simvastatin exerted an antiproliferative effect in renal cancer cells through cholesterol deprivation and prenylation-associated mechanisms. 31 …”
Section: Glycolysis Inhibitorsmentioning
confidence: 99%